Identification of geodiversity in Kalimpong District, India: A geospatial assessment using geodiversity index and multi-criterion decision analysis approach - Alok Sarkar; Sarfaraz Alam; Prasanya Sarkar; Pulak Barman; Shasanka Kumar Gayen (International Journal of Geoheritage and Parks)
The evaluation of geodiversity assessment is essential for preserving geoheritage, enhancing sustainable geotourism, and supporting conservation efforts in ecologically fragile regions. This research aims to analyse and explore the geodiversity of Kalimpong District, India, utilising a comprehensive geospatial analysis to identify areas of major geological importance for strategic planning for geotourism. This study conducts a thorough geospatial evaluation of geodiversity in India's Kalimpong District using the analytical hierarchy process (AHP) and the geodiversity index. Analysing diverse geospatial datasets, including energy of relief diversity, relief fragmentation diversity, geological diversity, drainage density diversity, topography roughness index, trekking routes diversity, waterfalls, lakes diversity, and soil diversity, it systematically characterizes the district's geodiversity. The analytical hierarchy process has been used to determine the main criterion's weight. We also grade the sub-criterion rank supplied by Zwoliński. The geodiversity index identifies areas with geodiversity potential. The geodiversity index aids in identifying and categorizing geodiversity zones into five levels: very high, high, moderate, low, and very low. The findings depict a varied landscape abundant in geological features, with distinct zones reflecting differing levels of geological richness. Notably, the presence of very high geodiversity zones around Neora Valley National Park highlights rugged terrains and dense forests. These zones not only allure tourists but also safeguard valuable geoheritage. This study accentuates the Kalimpong District's potential for geotourism development and stresses the significance of conservation endeavors to preserve its geological diversity. Leveraging its unique geological attributes, the district can establish sustainable geotourism destinations, fostering economic growth, cultural enrichment, and environmental preservation.